MOLECULAR CHARACTERIZATION OF CRUDE ENZYMATIC EXTRACT FROM ALGERIAN CAMEL ABOMASUM (CAMELUS DROMEDARIUS) - ISSELNANE, Souad; BOUDJENAH-HAROUN, Saliha; NOUANI, Abdelwahab; AHMED-ZENNIA, Saliha SI; BOUAZZA, Belaid; YABRIR, Benalia; MATI, Abderrahmane (Emirates Journal of Food and Agriculture, 2017)
Camel milk cannot be coagulated with bovine chymosin, most likely due to major variations between the primary k casein structures of the two species. Recently we have shown that the crude gastric extracts (CGE) from adults’ dromedaries provide satisfactory milk clotting activity and limited proteolytic activity towards the camel milk. In the present study, we have isolated and characterized the CGE from dromedary abomasum. The CGE was separated and purified by DEAE-Cellulose column chromatography and Sephacryl S200 gel filtration. From various collected fractions, we characterized two fractions (F3 and F5) presenting a milk clotting activity and were eluted at 0.1 M and 0.45 M NaCl respectively. Interestingly, the F5 fraction had the highest milk clotting activity. The purified enzyme was resolved as a single protein band on SDS-PAGE with a molecular weight estimated about 38 kDa which was not affected by the addition of β-mercaptoethanol. In native PAGE, the enzyme migrated as a single band having a high intensity with similar electophoretic mobility to that of porcine pepsin. Using two dimensional electrophoresis, we found that the band obtained from the native-PAGE was concentrated on a single spot, quite intense.